Writing high-quality case studies in sport science - Mujika, I.; Yamashita, D.; Strøm Solli, G. (International Journal of Sports Physiology and Performance, 2025)
Purpose: Sport-physiology and -performance research often relies on group designs that compare experimental and control groups and/or preintervention and postintervention results. This commentary highlights the key elements of a high-quality case study and provides clear guidelines for readers and authors of the International Journal of Sports Physiology and Performance. We propose 4 essential components. First, case studies should offer relevant and original insights by tackling novel issues and defining a clear purpose. Second, they must employ rigorous methodology, encompassing careful participant selection, comprehensive data collection from diverse sources (eg, interviews, surveys, physiological tests, training diaries, competition data), and deliberate data analysis that explicitly addresses factors influencing performance changes. Third, they should be well structured and engagingly presented to reach both academic and practical audiences. Finally, bridging the science-practice gap is vital, requiring and strengthening collaboration between researchers and practitioners to enable data-driven decision making and spark new hypotheses.